Culture and proficiency: the basis for a world language supplemental guide - Mahoney, Bailey (Kansas State University, 2023)
World Language educators today have a variety of topics to cover in a short amount of time. The struggle is trying to teach students to use the language proficiently and in culturally appropriate ways. Teachers of World Languages lack the time and resources to create activities that are both grounded in proficiency-based teaching practices and teach in-depth about the cultures of the languages. They often rely on the materials they have such as textbooks, workbooks, or worksheets. In this study, I use a content analysis to determine how Level 1 textbooks cover proficiency-based teaching and culture. Then, using the information obtained, I present a detailed curriculum supplemental guide for Level 1 language teachers. It is populated with authentic resources and examples that teachers can use to create and implement activities in the classroom. The guide gives teachers a chance to provide more proficiency-based activities and cultural information at a more in-depth level for their language learners.
Keywords: World languages; Culture; Proficiency; Language teaching